The multibeam linear ion accelerator: calculation and experiment - Gavrilov, N.M.; Gavrilov, M.K.; Bogatchenkov, D.A.; Ivanov, Е.V.; Komarov, D.A.; Strukov, J.N. (Вопросы атомной науки и техники, 2004)
The accelerating structure consisting of cylindrical screen with electrodes of coil types radialy disposed, which the current-conductive annuluses with tubes of driftage disposed azimuth of annulus are attached has been suggested. By way computer simulation were received the base-frequency of structure, shunt-impedance, distribution of field in the accelerating gaps. The experimental researched of frequencies generation coil in screen and field distribution functions were made.